تنمية مهارة القراءة في تطبيق إستراتيجية ذاكري لدى الطلاب في معهد “ المختاريّة “ سيرانج بانتين - Fawaz, Muhamad Aqil; Qodir, Abdul (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
Nemonic strategy is a method used to make it easier for students to understand the material presented by the teacher. This strategy is implemented at the Al-Mukhtariah Islamic boarding school located in Banten. The aim of implementing this strategy is to find out and improve students' ability to speak Arabic. This research aims to find out what the application of this mnemonic strategy is like and to find out the supporting and inhibiting factors in students' reading skills using Arabic. The researcher chose to use field research with a qualitative approach for his research method. The results of this research show the use of mnemonic strategies in improving Arabic reading skills and research that the use of mnemonic strategies can make students enthusiastic about memorizing vocabulary, and able to read Arabic writing fluently and correctly